Results of Using Alternating Presentation of Stereostimuli in Children with Functional Scotoma in Non-Paralytic Strabismus - S. I. Rychkova; V. G. Likhvantseva (Oftalʹmologiâ, 2021)
The work is devoted to one of the actual problems of modern strabismology — the study of the ability to stereo perception in children with non-paralytic strabismus.Purpose: to study the capability to stereovision with alternating presentation of stereostimuli in children with functional scotoma in non-paralytic strabismus.Patients and methods. 113 children with functional scotoma (FS) in non-paralytic strabismus were observed. We used stereostimuli with different characteristics in the following regimes of presentation: 1) the regime of simple monocular alternating (alternate presentation of an image for the right eye and the left eye); 2) the regime having an “empty” interval (black background) between monocular phases; 3) the regime having a binocular phase (a binocular image containing details corresponding to the stimuli for the right eye and the left eye) between monocular phases.Results. It was found that in 23 (20,3 %) children, the ability to stereo perception was completely absent. All these children had stable total FS (monocular vision). In the remaining 90 children (with unstable or regional FS), the ability to stereo perception was shown with some stimuli in some modes of their alternating presentation. For stimuli with a central arrangement of linear parts, the stereo effect was possible when they were presented in an alternating mode with an “empty” interval lasting from 20 to 70 ms in combination with the duration of monocular phases from 30 to 90 ms. For stimuli with a peripheral arrangement of linear elements, 22.1 % of children were able to stereo perception not only in the “empty” interval mode, but also in the simple alternation mode. At the same time, the greatest number of children capable of stereo perception was detected when using the mode with an “empty” interval of 30–60 ms and a duration of monocular phases of 40–60 ms. With random-dot stimuli, none of the children in this group were capable of stereo perception.Conclusion. Our results suggest that even in patients with FS in non-paralytic strabismus, stereo perception is possible under the conditions of alternating presentation of stimuli with certain characteristics. In this case, the most likely appearance of a stereo effect with stimuli containing peripheral linear elements that create a stereo effect when presented in an alternating mode with an empty interval between monocular phases.